Perspectives in cultural resource management
1 online resource (xiv, 300 pages)
Keywords: "New Perspectives in Cultural Resource Management describes the historic developments, current challenges, and future opportunities presented by contemporary Cultural Resource Management (CRM). CRM is a substantial aspect of archaeology, history, historical architecture, historical preservation, and public policy in the US and other countries.? Chapter authors are innovators and leaders in the development and contemporary practice of CRM.? Collectively they have conducted thousands of investigations and managed programs at local, state, tribal, and national levels. The chapters provide perspectives on the methods, policies, and procedures of historical and contemporary CRM. Recommendations are provided on current practices likely to be effective in the coming decades."--Provided by publisher.